PENGARUH LOKASI, MERCHANDISE, DAN ATMOSFER DALAM GERAI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA GELAEL SIGNATURE MALL CIPUTRA SEMARANG - Lumban Gaol, Maria Yesicca; Waloejo, Handoyo Djoko (Jurnal Ilmu Administrasi Bisnis, 2018)
The growth of modern ritel bussiness in Indonesia today has shown the rapid growing and has a promising in the future. This rapid growing causes the similar companies compete to attract and retain customers by using their marketing mix. One of the ritel bussiness that still survive until today is Gelael Signature.The purpose of this study is to determine the effect of location, merchandise, and store atmosphere to the purchasing decision at Gelael Signature Mall Ciputra Semarang. This type of research is explanatory research. Sampling technique using accidental with purposive technique. The number of samples taken as many as 100 respondents, which are the consumer of Gelael Signature. In this study assisted by IBM SPSS 21.0 system. The results showed that location influences the purchasing decision by contributing 32.2%. Merchandise influences the purchasing decision by contributing 15.5%. Store Atmosphere influences the purchasing decision by contributing 34.7%. Meanwhile, simultaneously location, merchandise, and store atmosphere influence to purchasing decision by donating 44.6% while the rest influenced by others. Based on the calculation of Test F shows that there is a significant influence between location, merchandise, and store atmosphere to the purchasing decision. This means the better location, merchandise, and store atmosphere, the higher the purchasing decision at Gelael Signature Mall Ciputra Semarang. Based on the results of the study, the researcher suggests that Gelael try to coordinate with the Mall to provide a spacious and secure parking lot, to providing stock of the goods and increasing the store atmosphere.